Pinch Analysis of Heat Exchanger Networks in A Simulated Milk Pasteurization Plant - Gelbert Jethro Sanyoto; Novita Ika Putri (JFCN: Journal of Food, Culinary, and Nutrition, 2025)
The dairy industry depends on milk pasteurization to achieve both product safety and nutritional value  through  its  controlled  heat  treatment  process.  However,  due  to  substantial  energy  usage, finding new methods which will boost operational efficiency is required. The research investigates the  Heat  Exchanger  Network  (HEN)  of  a  conventional  milk  pasteurization  facility  through  pinch analysis to minimize energy usage and production expenses. A High Temperature Short-Time (HTST) pasteurization system was simulated in SuperPro Designer v9.0 using data obtained from an existing plant with a capacity of 4,500 kg per hour. The hot and cold stream interactions were then analyzed using HINT v2.2 to find the pinch points and help redesign the heat recovery system. The analysis resulted  in  two  enhanced  HEN  configurations  which  became  Alternative  A  and  B.  The  analysis showed  Alternative  B  provided  the  optimal  solution  between  heat  recovery  and  cooling  demand requirements  which  would  result  in  $2,200  annual  utility  cost  savings.  The  $427,000  capital requirement  may  extend  the  payback  period  but its  success  depends  on  particular  factors  which include  local  energy  expenses  and  operational  efficiency.  The  research  demonstrates  that  pinch analysis provides essential value for  dairy processing operations because it helps improve energy efficiency and enables better sustainable decision-making.